Cerebrospinal fluid proteomic profiling in nusinersen-treated patients with spinal muscular atrophy - Keßler, Tobias; Latzer, Pauline; Schmid, Dominic; Warnken, Uwe; Saffari, Afshin; Ziegler, Andreas; Hayes, Jennifer; Möhlenbruch, Markus Alfred; Ulfert, Christian; Herweh, Christian; Wildemann, Brigitte; Wick, Wolfgang; et al. (Journal of neurochemistry, 2020)
The approved antisense oligonucleotide nusinersen demonstrated convincing clinical results in patients with 5q-linked spinal muscular atrophy (SMA) but predictive biomarkers are lacking to date.
First published: 06 January 2020
Gesehen am 12.01.2022